Covid-19 y estado de derecho: España. / COVID-19 and Rule of Law: Spain. - BELLO PAREDES, Santiago A (Utopía y Praxis Latinoamericana, 2020)
RESUMEN En este trabajo se analizan los efectos perjudiciales para los derechos humanos del Covid-19 en España y la necesaria reacción de los instrumentos legales del Estado de Derecho. ABSTRACT This paper analyzes the detrimental effects on human rights of the Covid-19 in Spain and the necessary reaction of the legal instruments of the Rule of Law.